Excursions in modern mathematics. - Tannenbaum, Peter, ....- (Harlow : Pearson Education Limited, 2014)
Excursions in Modern Mathematics introduces non-math majors to the power of math by exploring applications like social choice and management science, showing that math is more than a set of formulas. Ideal for an applied liberal arts math course, Tannenbaum's text is known for its clear, accessible writing style and its unique exercise sets that build in complexity from basic to more challenging. The Eighth Edition offers more real data and applications to connect with today's students, expanded coverage of applications like growth, and revised exercise sets. MyMathLab exercise sets are expanded and the new Ready To Go MyMathLab course makes course set-up even easier.
Keywords: Wiskunde (algemeen).